Influence of anodization of aluminum 2024 T3 for application in aluminum/Cf/ epoxy laminate. (1st March 2020) - Santos, Alberto L.; Nakazato, Roberto Z.; Schmeer, Sebastian; Botelho, Edson C.
Abstract: This work deals with the processing and characterization of aluminum/carbon fiber/epoxy composites obtained from anodized and non-anodized aluminum plates. In this work, the electrochemical treatment employed was the phosphoric anodization, after chemical stripping. After this treatment, the fiber metal laminate (FML) coupons were laminated, the aluminum plates were interleaved with CF/epoxy prepreg layers. The next step was the use of hot compression molding technique in order to prepare the FML with and without anodized aluminum surface treatment, for comparison purposes. Several characterization techniques were used, such as: impact and perforation resistance analysis, laminar, translaminar (Iosipescu) and compression shear strength, in addition to optical macroscopy. After the analysis of the results, it was verified that the electrochemical treatment slightly reduces the impact and the perforation resistance of FML studied, because a more adhered interface promotes larger internal tensions and consequently reduces the capacity to absorb energy until failure. However, the adhesion properties were shown to be superior in the composites produced with the anodized plates. Additionally, the treatment proved to be an important means of obtaining FMLs, since most of the plates produced with non-anodized aluminum delaminated after a few weeks in stock, while the FML obtained from anodized aluminum did not delaminate after months of their production.